2020
DOI: 10.1002/adom.202001885
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Step Anti‐Stokes Photoluminescence of CsPbX3 Nanocrystals

Abstract: Cesium lead halide (CsPbX3, X = Cl, Br, and I) perovskite nanocrystals (NCs) exhibit efficient anti‐Stokes photoluminescence (ASPL) upon sub‐gap single‐photon excitation, which has great potential for all‐solid‐state laser cooling. However, the mechanism responsible for the ASPL still remains elusive. Here, ASPL properties of CsPb(BrI)3 NCs and CsPbI3 NCs in inorganic solid matrix are investigated. Excitation wavelength‐ and power‐dependent ASPL demonstrates that it is a phonon‐assisted single‐photon process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…These values are comparable to those previously reported. , Notably, the electron–phonon interaction strength ( A EP ) of CsPb­(BrI) 3 NCs in the WG specimen is found to be 126.1 meV, much larger than that obtained from the NG specimen (84.4 meV) (Figure S3d), confirming that electron–phonon interaction in CsPb­(BrI) 3 NCs is enhanced due to the water quenching-induced distortion of [PbX 6 ] octahedra. It has been reported that the distortion of the [PbX 6 ] octahedra can enhance the tail states, leading to the localization of photogenerated charge carriers via the interaction with phonons . Feldmann et al reported that the incorporation of Mn 2+ ions into the CsPb­(ClBr) 3 NCs breaks the lattice periodicity, leading to charge carrier localization and enhancing the intrinsic radiative recombination .…”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These values are comparable to those previously reported. , Notably, the electron–phonon interaction strength ( A EP ) of CsPb­(BrI) 3 NCs in the WG specimen is found to be 126.1 meV, much larger than that obtained from the NG specimen (84.4 meV) (Figure S3d), confirming that electron–phonon interaction in CsPb­(BrI) 3 NCs is enhanced due to the water quenching-induced distortion of [PbX 6 ] octahedra. It has been reported that the distortion of the [PbX 6 ] octahedra can enhance the tail states, leading to the localization of photogenerated charge carriers via the interaction with phonons . Feldmann et al reported that the incorporation of Mn 2+ ions into the CsPb­(ClBr) 3 NCs breaks the lattice periodicity, leading to charge carrier localization and enhancing the intrinsic radiative recombination .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Upon SGE, the maximal upconversion energies (difference between the ASPL peak energy and excitation energy) are 163.7 meV for the NG specimen and 174.3 meV for the WG specimen. These features of ASPL from the NG and WG specimens are consistent with our previous research and other literature, , confirming that the ASPL of the CsPb­(BrI) 3 NCs in the NG and WG specimens is closely related to the Urbach tail states.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations